New York Jets - Frisch, Aaron, 1975- (Mankato, Minn. : Creative Education, 2011)
"An elementary look at the New York Jets professional football team, including its formation in 1960, most memorable players, Super Bowl championship, and stars of today"--Provided by publisher.
Includes index.
Keywords: New York Jets (Football team) -- Juvenile literature